Differential impact of affective and cognitive attributes on preference under deliberation and distraction - Wang, Zuo-Jun; Chan, Kai-Qin; Chen, Jiao-Jiao; Chen, Ai; Wang, Fei (Frontiers in Psychology, 2015)
Two experiments were designed to test the hypothesis that affective information looms relatively larger than cognitive information when individuals are distracted for a period of time compared to when they engage in deliberative thinking. In two studies, participants were presented with information about 4 decision alternatives: An affective alternative that scored high on affective attributes but low on cognitive attributes, a cognitive alternative with the opposite trade-off, and two fillers. They were then asked to indicate their attitudes towards each of four decision alternatives either immediately, after a period of deliberation, or after a period of distraction. The results of both experiments demonstrated that participants significantly preferred the affective alternative to the cognitive alternative after distraction, but not after deliberation. The implications for understanding when and how unconscious thought may lead to better decisions are being discussed.